Message - Najib, Ahmad (Universal Journal of Pharmaceutical Research, 2020)
With the development of science and technology, it is now possible to exchange knowledge more broadly, especially with the presence of the Universal Journal of Pharmaceutical Research (UJPR) discussing science which is currently the main topic of discussion including pharmaceutical science. The existence of this journal is very helpful for communication between researchers in various parts of the world due to information systems which already online allow access to obtain the latest knowledge on this topic will be greater with the existence of this journal to open a wider network among the ways in which existing researchers. This journal is very useful to support the continuity of development of Pharmacy in particular and the dissemination of knowledge in general with editorial originating from various countries. UJPR guarantees the quality of the authors to make publications because editors who have extensive experience with various pharmaceutical backgrounds and also from various countries is a guarantee that this journal is a journal that has a good reputation. So that there is no doubt for researchers to publish the results of research they have done especially with the indexation of journals by a large database so as to increase the trust this journal deserves to publish your valuable research results. Hope in coming days UJPR will get indexing with some more reputable agencies.